Acceptability and potential effectiveness of commercial portion control tools amongst people with obesity. Issue 11 (15th December 2016) - Almiron-Roig, Eva; Domínguez, Angélica; Vaughan, David; Solis-Trapala, Ivonne; Jebb, Susan A.
Abstract: Exposure to large portion sizes is a risk factor for obesity. Specifically designed tableware may modulate how much is eaten and help with portion control. We examined the experience of using a guided crockery set (CS) and a calibrated serving spoon set (SS) by individuals trying to manage their weight. Twenty-nine obese adults who had completed 7–12 weeks of a community weight-loss programme were invited to use both tools for 2 weeks each, in a crossover design, with minimal health professional contact. A paper-based questionnaire was used to collect data on acceptance, perceived changes in portion size, frequency, and type of meal when the tool was used. Scores describing acceptance, ease of use and perceived effectiveness were derived from five-point Likert scales from which binary indicators (high/low) were analysed using logistic regression. Mean acceptance, ease of use and perceived effectiveness were moderate to high (3·7–4·4 points). Tool type did not have an impact on indicators of acceptance, ease of use and perceived effectiveness ( P >0·32 for all comparisons); 55 % of participants used the CS on most days v . 21 % for the SS. The CS was used for all meals, whereas the SS was mostly used for evening meals. Self-selected portion sizes increased for vegetables and decreased for chips and potatoes with both tools. Participants rated both tools as equally acceptable, easy to use and with similar perceived effectiveness. Formal trials to evaluate the impact of such tools on weight control are warranted.